THE ROLE OF THE LEADER IN THE PROCESS OF OVERCOMING COMMUNICATION BARRIERS IN THE NEW ERA OF INDUSTRY 4.0 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Modern challenges in the new era of Industry 4.0 confront leaders with communication barriers. Barriers are factors that block or negatively change successful communication in teams. They cause stress, which is the result of dynamically developing technologies and advanced automation of processes. Depending on the leader, barriers can be temporary and surmountable, but they can be permanent and more difficult to overcome. The proposed key factors of a leader are closely related to leadership skills in the process of overcoming communication barriers. .Taking into account the specific characteristics of the industry and the growing role of the leader in the process of making management decisions, an algorithm is proposed for successfully overcoming communication barriers in the new era of Industry 4.0. The purpose of the report is to analyze the barriers and systematize the key factors for successful communication in the team and the role of the leader in developing Fig. 1. А  model of an algorithm for successfully overcoming communication barriers.